Effect of increasing levels of phytase on performance, prececal nutrient digestibility, intestinal mucosa physiology and immune response in broiler chickens from 1 to 21 days of age - B. Martínez-Vallespín; P. Ader; J. Zentek (Poultry Science, 2025)
Phytic acid is the primary storage form of phosphorus (P) in plants and broiler chickens have a limited capability for its utilization. The supplementation of exogenous phytase in feed enables broilers to use the phytate-bound P. The current study evaluated the supplementation of increasing levels of a bacterial hybrid 6-phytase (500, 1,500 and 3,000 FTU/kg feed; groups LP2, LP3 and LP4, respectively) to a low-P, phytate-containing broiler chicken diet (LP1), fed from day 1 to 21 of age. Statistical analysis used a general linear model with linear and quadratic contrasts to assess phytase-level trends. The efficacy of the phytase on performance and ileal digestibility was demonstrated with linear increases in body weight (BW), BW gain, feed intake and apparent ileal digestibility of most of the amino acids, as well as of P (P < 0.05). The increasing levels of phytase led to a linear decrease of jejunal and caecal crypt depth when corrected for BW (P < 0.05), and to a linear decrease of the villus height:crypt depth ratio (P = 0.028). Secretory IgA measured in jejunum digesta showed a trend to a linear increase with the increasing levels of phytase (P = 0.092). The measurement of d-glucosamine and d-galactosamine as markers of mucus secretion in ileum digesta showed differences for d-glucosamine only, with a linear increase of this marker due to the phytase supplementation (P = 0.017). Finally, a trend for increased ex situ glucose transport was observed in Ussing chambers when tissue of the jejunal mucosa of LP1 group was compared with that of LP4 group (P = 0.079). Quadratic effects suggest a stabilizing response in most traits beyond a certain phytase level, indicating a biological plateau. In conclusion, the use of increasing doses of exogenous bacterial hybrid 6-phytase up to 3,000 FTU/kg in broilers from day 1 to 21 of age improved performance and nutrient digestibility as well as some traits related to intestinal physiology and immune response.